TATA LAKSANA EVALUASI SISTEM APLIKASI MANG BAGJA DI SEKRETARIAT DAERAH KOTA BANDUNG - Tubagus Azkal Ersa Azkiya; Saifullah Zakaria; Jovanscha Qisty Adinda (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Bureaucratic reform efforts aim to enhance accountability and transparency in the administration of local government. The Bandung City Government has implemented the MANG BAGJA application system as a supporting instrument for evaluating civil servant (ASN) performance. However, in practice, evaluations of this system still reveal several issues, particularly related to user experience, the accuracy of performance data, and a tendency toward predominantly administrative use.This study aims to analyze the governance of the evaluation of the MANG BAGJA application system within the Regional Secretariat of Bandung City, with an emphasis on the perspective of ASN users. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data analysis is conducted using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, positioned as a qualitative conceptual framework, focusing on the constructs of performance expectancy and social influence.The findings indicate that the use of the MANG BAGJA application by ASN is not yet fully based on perceived benefits for improving performance, but is still largely influenced by administrative demands, leadership directives, and bureaucratic work norms. This condition results in the system’s evaluative function not being optimally utilized to substantively support ASN performance assessment.This study highlights the importance of user experience–based system evaluation in the governance of government applications. The findings are expected to serve as a basis for improving the governance of ASN performance evaluation systems so that they are more oriented toward work benefits, accountability, and the quality of personnel decision-making.